Mobile application for testing fine motor skills of children - Abousetta, V. (Graz, Austria, 2020)
The mobile application has been adapted for children enables develop fine motor skills by registering basic physical parameters during testing. The testing process on smartphone is execution different tasks with low-level and high-level complications - reiteration of the fingers of the trajectory of the object movements. In addition, the development of specialized tests based on the current performance of fine motor skills is an important scientific task.
Keywords: fine motor skills; test; children; mobile application